HUBUNGAN PENGETAHUAN, SIKAP DAN PRAKTIK HIDUP BERSIH DAN SEHAT DENGAN STATUS GIZI PADA REMAJA - Damanik, Kanaya Yori; Rukmana, Erni; Fransiari, M. Edwin; Nurfazriah, Latifah Rahman (Jurnal Andaliman: Jurnal Gizi Pangan, Klinik dan Masyarakat, 2023)
Adolescents are one of the age groups that are vulnerable to experiencing nutritional problems because they can determine their own lifestyle. Apart from diet, clean and healthy behavior is one of the indirect causes that influences nutritional status. Knowledge about clean and healthy living that teenagers have can determine their clean and healthy behavior attitudes and practices. Low clean and healthy behavior can be a risk factor for infectious diseases which can reduce nutritional status. This study aims to examine the relationship between knowledge, attitudes and practices of clean and healthy behavior and the nutritional status of adolescents. This research uses a cross-sectional study. The research was conducted in June-November 2023 at Al-Washliyah 1 Private High School, Medan City and Bandung Foundation High School, Deli Serdang Regency. The selection of research locations was carried out using purposive sampling. The research population was students in grades X to XII aged 14-18 years in both schools. The sampling technique used cluster sampling, the total subjects were 100 students from each school. Data was collected through questionnaire interviews in the form of characteristics, knowledge, attitudes and practices of clean and healthy behavior. Nutritional status data was obtained by directly measuring body weight using a digital scale and height using a microtoise and then determined using a z-score from the body mass index according to age (BMI/U). Data analysis was carried out using the Spearman Test. As many as 31% of teenagers have abnormal nutritional status (undernutrition, overnutrition and obesity). The bivariate test results showed that there was a significant relationship between knowledge (p=0.005), attitudes (p=0.001), and practice (p=0.000) of clean and healthy behavior and adolescent nutritional status. As many as 65.5% of teenagers with low clean and healthy behavior attitudes have abnormal nutritional status. Adolescents need to pay attention to clean and healthy behavior in their daily lives to help obtain good nutritional status.Keywords—Knowledge, Clean and Healthy Behavior, Adolescents, Nutritional Status